Improved prediction of pre-camber of post-tensioned prestressed i-beam - Wahid, Omar, Assoc. Prof. Dr.; Tan, Pui Lai; Lee, Poh Hua; Roslina, Omar (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/